Application of Affine Estimators to Single Tone Frequency Estimation - Gama, Fernando (2012)
Affine estimation has emerged as a promising technique to reduce the mean squared error (MSE) between the estimated parameters and the true value of these parameters. The aim of this paper is to obtain an affine estimator for the frequency of a complex sinusoid corrupted by white gaussian noise. Additionally, an adaptive technique is presented. The simulation results clearly show that affine estimators have better performance than unbiased estimators such as the maximum likelihood estimator (MLE) and the Fu-Kam approximation.